The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1177/0162643418754530
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effects of Modality and Multimedia on the Learning Performance of College Students With Dyslexia

Abstract: There has been a lack of research on how people with individual differences learn with multimedia materials, in particular with regard to individuals with dyslexia. Dyslexia is a learning disability characterized by subpar ability in reading, spelling, writing, word recognition, and phonological decoding. This population could potentially benefit from multimedia learning materials according to the cognitive theory of multimedia learning and Orton–Gillingham multisensory instructional approach. This study exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 56 publications
2
5
0
Order By: Relevance
“…If the modality principle of the CTML were valid when applied to the video condition, students would perform better in the video lecture than the website condition. Our results could indicate that the modality principle is not valid for students with dyslexia, which was also discovered in a study by Wang et al (2018). Our results are also consistent with Beacham and Alty (2006), who found that neither of the provided multimedia combinations (onscreen text and picture versus narration and picture) was significantly effective for students with dyslexia.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…If the modality principle of the CTML were valid when applied to the video condition, students would perform better in the video lecture than the website condition. Our results could indicate that the modality principle is not valid for students with dyslexia, which was also discovered in a study by Wang et al (2018). Our results are also consistent with Beacham and Alty (2006), who found that neither of the provided multimedia combinations (onscreen text and picture versus narration and picture) was significantly effective for students with dyslexia.…”
Section: Discussionsupporting
confidence: 90%
“…In view of the findings, we would suggest that it be repeated in future on larger samples. This is particularly important because our results are to some extent aligned with those obtained from other studies on students with dyslexia learning from multimedia in which the sample size was also relatively small (Alty et al, 2006, Wang et al, 2018. In the future, qualitative measures should be incorporated in the research design (e.g., interviews on the learning experience in different multimedia combination) as this would provide additional value, especially because studies involving special educational needs students are often, as stated before, conducted on small samples.…”
Section: Discussionsupporting
confidence: 87%
“…Students were encouraged to analyse the different examples via guided discussion to increase comprehension and point them towards relevant cultural, linguistic, topic-based and assessment-related information, building on previous material and providing a staged introduction to the necessary concepts to complete the task succesfully. This was supplemented by the provision of further resources via the VLE, which also allowed students to reinforce their learning via the opportunity to review material as many times as they wished, an invaluable aide memoire for dyslexic students (Kormos & Smith, 2012;Wang et al, 2018).…”
Section: How the Assessment Workedmentioning
confidence: 99%
“…This has clear implications for second language learning where standard classroom practices are not always helpful: This is particularly true of natural or communicative methodologies, in which students are expected to infer meaning from the context and receive less instruction in sound-system and syntactical or grammatical rules (Nijakowska, 2010, p.127;Schneider & Crombie, 2004, p.16). Various studies have shown instead that multisensory approaches or "the simultaneous presentation of linguistic material with the use of as many sensory channels as possible" (Nijakowska, 2010, p.125) are of much more benefit to dyslexic students (see Kast et al, 2011;Wang et al, 2018). Other beneficial approaches include: direct and explicit instruction in the sound-symbol, grammatical, lexical, semantic and sociopragmatic systems of the language (metacognitive strategies); increased exposure to print in the L2, combined with listening and speaking work on the same text (multisensory input); usage of the L2 as the language of instruction in the classroom, keeping the native language for clarification of areas of special difficulty; increased usage of repetition developed across structured stages; the use of mnemonics; and frequent review of elements, since dyslexics "rely on long-term memory, requiring practice and concrete examples for understanding" (Waterfield, 2002, p.22).…”
Section: Introductionmentioning
confidence: 99%
“…It is a commonly held assumption that multimedia materials aid learning of students with reading difficulties [7], yet only recently have studies empirically demonstrated that multimedia instruction is more beneficial than single media instruction for students who have reading difficulties. Wang et al [8] examined how college students with specific reading disabilities performed in multimedia (text and picture) vs. single media (text-only) conditions and found that students answered comprehension questions more accurately in the multimedia condition than in the single media condition. Similarly, Kim and Lombardino [9] reported that college students with reading deficits benefitted more from multimedia (narration-picture) than single media (narration-only) instruction.…”
Section: Introductionmentioning
confidence: 99%